Clinical Characteristics of Bloodstream Infection in Immunosuppressed Patients: A 5-Year Retrospective Cohort Study - Lin, Hongxia; Yang, Lili; Fang, Jie; Gao, Yulian; Zhu, Haixing; Zhang, Shengxiong; Summah, Hanssa Dwarka; Shi, Guochao; Sun, Jingyong; Ni, Lei; Feng, Yun (Frontiers in Cellular and Infection Microbiology, 2022)
Introduction Immunosuppressed patients with bloodstream infection are at risk of mortality. Our objective was to assess the independent risk factors of bloodstream infection with mortality in immunosuppressive states. Methods The medical data of a total of 896 patients who were hospitalized in our hospital were collected from January 2015 to December 2019. Evaluation of the independent risk factors of mortality was done by univariate and multivariate logistic regression analyses. Results Of the 896 immunosuppressed patients with bloodstream infection, 698 had over 60-day survivals and 198 had 60-day mortality. In our study, PCT (mean ±; standard: 11.40 ±; 31.89 µg/l vs. 62.45 ±; 17.10 µg/l, p = 0.007) and presence of age >60 years (40% vs. 14.19%, p = 0.001) were significantly different between situations with and without 60-day survivals in both univariate and multivariate logistic regression analyses. Age >60 years and PCT could be used as indicators for bloodstream infection with 60-day death in immunosuppressive states; the OR (95% CI) were 1.532 (1.099–2.135) and 2.063 (1.413–3.013), respectively. In different subgroups, PCT and age were also independent risk factors of blood system diseases, Klebsiella pneumoniae infection, diabetes, and ICU-stay subgroups. Conclusions Age and PCT were independently associated with mortality in immunosuppressive states, which may help to identify the highly risky situation of bloodstream infection in immunosuppressive states.